An evaluation of Korean SNS in China : A case study of Cyworld - YANG, NAYOUNG (2010)
This paper aims to 1) identify the difference between Chinese and Koreas in terms of motivations and evaluations in Cyworld and 2) examine differences between attitudes (positive and negative) and between cultural proximities (high and low) with regard to Chinese motivations and evaluations. The data were collected from Chinese (n=50) and Korean students (n=50) who study in Nottingham university. Factor analysis identified four dimensions of Chinese motivations (e.g. Interest information seeking, friendship, self-pursuit and relaxation) and three dimensions of evaluations (e.g. Interest information seeking, entertainment and negative recognition). When it comes to attitude toward Korea, motivations of positive attitude group showed higher mean of interest information seeking, friendship and self-pursuit compared to negative group. However, with regard to Chinese evaluations, only information seeking showed difference between high and low attitude. On the other hand, between cultural proximities, there were differences among all the motivations and evaluations. A Discussion was made from the results and limitations and directions for further researches were discussed.